2002
DOI: 10.1128/aem.68.5.2610-2613.2002
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Growth Temperature Dependence in the Adhesion of Candida parapsilosis to Polystyrene

Abstract: The purpose of this work was to study the adhesion to polystyrene of two Candida parapsilosis strains, grown at 22 and 37°C, in terms of hydrophobicity, surface charge, and interaction free energy. Growth temperature changed the surface properties of microorganisms, yielding a good correlation between thermodynamic predictions and adhesion behavior.Candida parapsilosis has emerged as an important nosocomial pathogen (16,20,24) with clinical implications, all of which usually occur in association with invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 22 publications
2
31
0
4
Order By: Relevance
“…An earlier study suggested that cell metabolism appeared to be essential for the maintenance of cell adhesion at higher temperatures [41]. However, it should be stressed that the effect of growth temperature on the initial microbial adhesion is also shown to be strongly dependent on the bacterial strain [42]. Previous studies involving the characterization of nonspecific bacterial adhesion to biomaterial surfaces observed that the initial cell adhesion and reversible cellular association with the surface occurred after a lag period of about 1-2 h [43,44].…”
Section: Early Biofilm Formationmentioning
confidence: 97%
“…An earlier study suggested that cell metabolism appeared to be essential for the maintenance of cell adhesion at higher temperatures [41]. However, it should be stressed that the effect of growth temperature on the initial microbial adhesion is also shown to be strongly dependent on the bacterial strain [42]. Previous studies involving the characterization of nonspecific bacterial adhesion to biomaterial surfaces observed that the initial cell adhesion and reversible cellular association with the surface occurred after a lag period of about 1-2 h [43,44].…”
Section: Early Biofilm Formationmentioning
confidence: 97%
“…These modifications may result in a change in cell surface hydrophobicity. The hydrophobicity of the microbial cell surface plays a critical role in the adherence of bacteria to a wide variety of hydrophobic surfaces (e.g., polystyrene) (33,34). Because adherence of bacteria to the surface is the first step in biofilm formation, it is expected that an increase in cell surface hydrophobicity is accompanied by nonadapted treated cells; (G and H) adapted treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…In drinking water distribution systems, microbial adhesion will initiate biofilm formation, exacerbating contamination of drinking water, reducing the aesthetic quality of potable water, increasing the corrosion rate of pipes sion step can be interpreted in terms of Lifshitz-van de Waals forces (LW) and acid-base forces (AB) (Smets et al 1999, Gallardo-Moreno et al 2002a. When a microorganism and a surface enter into direct contact the water film present between the interacting entities has to be removed.…”
mentioning
confidence: 99%